PELAKSANAAN DIKLAT DAN KOMPENSASI PADA PT. BUMI SUMBER KARYA - W Widarto; Alexander Wilar (STIA Bina Banua Banjarmasin, 2019)
The purpose of this study was to find out about the implementation of training and compensation at PT. Bumi Sumber Karya, to find out the inhibiting factors for the implementation of training and compensation and to provide alternative solutions to overcome these inhibiting factors. The research method used was descriptive with data analysis techniques using qualitative analysis The results of the study showed the implementation of training on PT. Bumi Resources works made through on the job training and of the job training. For in the job training such as training of drivers and operation of the machine and the operation of GPS and related applications. For of the job training include certification training of the head of mine engineering and trainings of member Port. The implementation of compensation covers financial, which is principal salary, job allowance, achievement wages, health benefits, feast day allowance, dining allowances, work transport, production allowances, leave money, MES employees, recreational facilities along the tour, While financial compensation includes the granting of Charter awards and verbal recognition through certain forums. The implementation of the training is the information and frequency of the training implementation, especially that held by other parties erratic time, employee loyalty, the time of training with target work is sometimes unbalanced and budget funds Limited. The blocking implementation factor is a technical problem and there is no raw regulation in the provision of benefits. Alternative solution Overcoming training and compensation factors is proactive looking for information or cooperation with third parties, increasing employee loyalty, synergity between training with target achievement. Need a priority program for training. For compensation needs to be made the standard of reward from achieving more targets and there must be a basic regulation of the provision of benefits-allowances so more guaranteed certainty. Tujuan dari penelitian ini adalah untuk mengetahui Pelaksanaan diklat dan pemberian kompensasi pada PT. Bumi sumber karya, untuk mengetahui faktor penghambat pelaksanaan diklat dan pemberian kompensasi serta untuk memberikan alternatif solusi mengatasi faktor penghambat tersebut. Metode penelitian yang digunakan adalah deskriptif dengan teknik analisa data menggunakan analisa kualitatif Hasil penelitian menunjukan Pelaksanaan diklat pada PT. Bumi sumber karya selama ini dilakukan melalui on the job training dan of the job training. Untuk in the job training seperti diklat pengemudi dan pengoperasian alat berat dan pengoperasian GPS dan aplikasi terkait. Untuk of the job training meliputi pelatihan sertifikasi kepala teknik tambang dan diklat ahli kepelabuhanan. Pelaksanaan kompensasi meliputi Finansial yaitu gaji pokok, tunjangan jabatan, upah prestasi, tunjangan kesehatan, tunjangan hari raya, tunjangan makan, transport kerja, tunjangan produksi, uang cuti, mes karyawan, sarana olah ragaserta wisata bersama, sedangkan kompensasi finansial meliputi pemberian piagam penghargaan dan pengakuan-pengakuan secara lisan melalui forum tertentu. Faktor penghambat pelaksanaan diklat adalah informasi dan frekwensi pelaksanaan diklat terutama yang diselenggarakan pihak lain waktunya tidak menentu, Loyalitas Karyawan, Waktu diklat dengan target pekerjaan kadang belum seimbang dan Anggaran dana terbatas. Faktor Penghambat Pelaksanaan Kompensasi adalah masalah teknis dan belum ada peraturan baku dalam pemberian tunjangan. Alternatif Solusi Mengatasi Faktor Penghambat Diklat dan Kompensasi adalah Proaktif mencari informasi atau menjalin kerjasama dengan pihak ke tiga, Meningkatkan loyalitas karyawan, Melakukan sinergitas antara diklat dengan pencapaian target. Perlu program prioritas untuk diklat. Untuk kompensasi perlu dibuat standar pemberian reward dari pencapaian target yang lebih dan harus ada peraturan baku adanya pemberian Tunjangan-tunjangan jadi lebih menjamin kepastian.